A interação universidade com as empresas incubadas: uma análise das empresas graduadas e incubadas pela incubadora da Unidavi - Pasqualini, Jairo Luis (Universidade do Vale do Rio dos Sinos, 2018)
The Works presents an analysis of the companies graduated and incubated by the incubator of Unidavi that takes the name of GTEC and the interaction of the companies with the mentioned university center as well as the contribution of the program for the enterprise development and also as a model other university institutions. By means of a case study involving the GTEC and its incubated and graduated companies, it was investigated the way in which the incubation processes occurred until then; the benefits and the barriers of the processes, in order to identify possible actions for the growth of the interaction between university and the companies and the success of the program and of the own companies. The chosen theme comes from the fact that entrepreneurship and innovation have been raised in academia and business as a matter of value and relevance, let alone in the competitive market that they see installed. Thus, the university began to be seen by society, especially in the business environment, as an alternative in the search for bets and solutions to face social and economic difficulties. The incubation program is a way for university and business society to develop innovation, increase competitiveness and in that sense, strengthen the economic and social base of the region. Through research by the model of semi-structured with diagnosis of positive and negative feelings, interviews conducted to the partners of the companies and to those responsible for the incubation program of the GTEC and Unidavi, it was concluded that the incubation program was successful with the companies already graduated, presenting nowadays with the some shortcomings and barriers to be overcome. Issues such as the limitation, deficiency and low interaction of companies graduated and incubated with Unidavi, as well as the lack of greater institutional support in the program and the search for innovation need to be corrected through means, it is believed the expansion of the relation of companies with Unidavi and the insertion of the program in the undergraduate courses and of all human and technical structure that the university center has.
Keywords: Incubadora; Empresas; Interação; Incubator; Companies; Interaction; ACCNPQ::Ciências Sociais Aplicadas::Administração